Three decades of telemedicine in Brazil: mapping the regulatory framework from 1990 to 2018 - Silva, Angélica Baptista (2020)
Fundação Oswaldo Cruz. Escola Nacional de Saúde Pública Sergio Arouca. Departamento de Direitos Humanos, Saúde e Diversidade Cultural. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Escola Nacional de Saúde Pública Sergio Arouca. Departamento de Políticas de Medicamentos e Serviços Farmacêuticos. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Escola Nacional de Saúde Pública Sergio Arouca. Instituto de Comunicação e Informação Científica e Tecnológica em Saúde. Rio de Janeiro, RJ, Brasil.